Factors determining the location decision: Analysis of location choice preferences of the ICI-1000 companies with the nested logit model - Büşra Akın; Ümit K. Seyfettinoğlu (Central Bank Review (CBR), 2022)
The aim of this study is to analyze the location decisions of the manufacturing industry companies in the ICI Top 500 and Second Top 500 Industrial Enterprises (ICI-1000) for the year 2018. The location choice model developed accordingly is based on the assumption that companies choose the location of their production facilities with 'the goal of profit maximization, and that this decision is influenced by both internal (company-specific) and external (sectoral and regional) factors'. The empirical analysis is conducted utilizing the nested logit estimation method and a large data set containing information on 909 manufacturing industry companies among ICI-1000, sub-sectors and location alternatives. The results support the views of Neoclassical and Institutional location approaches. The location decisions of the companies are affected by the characteristics specific to the company, sector and location. The ICI-1000 companies in the study tend to locate in areas with high market power and market growth, qualified and abundant labor, high sectoral growth and diversity and good geographical and physical conditions. The impact of these factors on company location preferences varies depending on the technological intensity of the industry in which they operate (high/low). Companies operating in high-tech (high, medium-high, medium-low) sectors choose places with a diversified and deepened labor pool, sectoral diversity and knowledge diffusion. On the other hand, the effect of specialization that emerged with localization economies is crucial in the location decisions of companies in low-tech sectors.
Keywords: D22; R30; L60; C35; 330; Firm behavior; Firm location; Manufacturing; Nested logit model